Caracterización bromatológica de pellets elaborados a partir de subproductos agropecuarios para la alimentación de bovinos - López-Varela, David (2017)
With the purpose of nutritionally characterize a mixture of Cassava (CV) (Manihot esculenta), Poultry Manure (PM), Soy Flour (SF), Rice Flour (RF), Soy Oil (SO), Cultivation of lactobacilli (CL), we performed a bromatological analysis to pellets from raw material, with the following levels of incorporation in the mixture:, (CV) 15%, (PM) 30%, (SF) 15%, (RF) 30%, (SO) 5%, (CL) 5%. The bromotological study was done in the Department of Animal Science (DZO) in the federal university of Viçosa (UFV), Brazil. We performed testing on raw protein(RP), Dried Material (DM), Ash Content(AC), Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), Ethereal extract (EE), Organic Material (OM), Non- Fibrous Carbohydrates (CNF), for which we obtained the following results: PC: 13,16%, MS: 93,61%, AC: 29,98%, FDN: 30,91%, FDNcp: 16,88%, FDA: 21,20%, FDAcp: 11,90%, EE: 12%, MO: 70,02%, CNF: 27,98%. We concluded that the pellets from the mixture of sub-products show nutritional characteristics with high potential in the use of alternatives for feeding cattle in times of scarcity using agricultural sub-products available in the northern region of Costa Rica.